Volume 9: Eighth International Conference on Creep and Fatigue at Elevated Temperatures 2007
DOI: 10.1115/creep2007-26501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Creep Deformation Mechanism of Heat Resistant Steel by Stress Change Test

Abstract: In order to evaluate creep deformation mechanism of heat resistant steels, stress change tests were conducted during creep tests. In this study, it was confirmed that the dislocation behavior during the creep tests was in viscous manner, because no instantaneous plastic strain was observed at stress increments. Transient behavior was observed after stress changes for all kinds of steel in this work. Mobility of dislocation was evaluated by the observed backward creep behavior after stress reduction. Internal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…It is thus concluded that there are no essential differences in the dislocation densities obtained by a TEM observation and an SCH method, apart from the case for a detailed investigation of causes of the differences between individual cases. However, it should be remembered that the dislocation densities measured by Hayakawa et al (1970;2007a;2007b) for alloy steels employing an SCH method are relatively low.…”
Section: Dislocation Densitymentioning
confidence: 99%
See 4 more Smart Citations
“…It is thus concluded that there are no essential differences in the dislocation densities obtained by a TEM observation and an SCH method, apart from the case for a detailed investigation of causes of the differences between individual cases. However, it should be remembered that the dislocation densities measured by Hayakawa et al (1970;2007a;2007b) for alloy steels employing an SCH method are relatively low.…”
Section: Dislocation Densitymentioning
confidence: 99%
“…I and II using these parameter constants. The dislocation densities were reported for specimens that crept at temperatures higher than the test temperatures used by the NIMS, but the data point obtained at 630 ℃ and 60 MPa by Hayakawa et al (2007a) (solid square) lies near the regression line at 630 ℃ for the NIMS data. There is a difference between the MCRs of Hayakawa et al and the NIMS at 630 ℃, but such a difference should be metallurgically allowed.…”
mentioning
confidence: 99%
See 3 more Smart Citations